Differential mitochondrial and cellular responses between H vs. J mtDNA haplogroup-containing human RPE transmitochondrial cybrid cells. (June 2022) - Panvini, Ana Rubin; Gvritishvili, Anzor; Galvan, Hannah; Nashine, Sonali; Atilano, Shari R.; Kenney, M. Cristina; Tombran-Tink, Joyce
Abstract: Mitochondrial dysfunction is associated with several retinal degenerative diseases including Age-related Macular Degeneration (AMD). Human mitochondrial DNA (mtDNA) haplogroups are inherited from a common ancestral clan and are defined by specific sets of genetic differences. The purpose of this study was to determine and compare the effects of mtDNA haplogroups H and J on transcriptome regulation and cellular resilience to oxidative stress in human RPE cytoplasmic hybrid (cybrid) cell lines in vitro. ARPE-19 cybrid cell lines containing mtDNA haplogroups H and J were created by fusing platelets obtained from normal individuals containing H and J haplogroups with mitochondria-deficient (Rho0) ARPE-19 cell lines. These cybrids were exposed to oxidative stress using 300 μM hydrogen peroxide (H2 O2 ), following which mitochondrial structural dynamics was studied at varying time points using the mitochondrial markers - TOMM20 (Translocase of Outer Mitochondrial Membrane 20) and Mitotracker. To evaluate mitochondrial function, levels of ROS, ΔΨm and [Ca 2+ ]m were measured using flow cytometry, and ATP levels were measured using luminescence. The H and J cybrid cell transcriptomes were compared using RNAseq to determine how changes in mtDNA regulate gene expression. Inflammatory and angiogenic markers were measured using Luminex assay to understand how these mtDNAs influenced cellular response to oxidative stress. Actin filaments' morphology was examined using confocal microscopy. Following exposure to H2 O2 stress, the J cybrids showed increased mitochondrial swelling and perinuclear localization, disturbed fission and fusion, increased calcium uptake (p < 0.05), and higher secreted levels of TNF-α and VEGF (p < 0.001), compared to the H cybrids. Calcium uptake by J cybrids was reduced using an IP3R inhibitor. Thirteen genes involved in mitochondrial complex I and V function, fusion/fission events, cellular energy homeostasis, antioxidant defenses, and inflammatory responses, were significantly downregulated with log2 fold changes ranging between −1.5 and −5.1. Actin levels were also significantly reduced in stressed J cybrids (p ≤ 0.001) and disruption in actin filaments was observed. Thirty-eight genes involved in mitochondrial and cellular support functions, were upregulated with log2 fold changes of +1.5 to +5.9 in J cybrids compared to H cybrids. Our results demonstrate significant structural and functional differences between mtDNA haplogroups H vs. J -containing cybrid cells. Our study suggests that the J mtDNA haplogroup can alter the transcriptome to increase cellular susceptibility to stress and retinal degenerations. Highlights: The stressed J cybrids showed increased calcium uptake, and higher levels of TNF-α and VEGF, compared to the H cybrids. The stressed J cybrids showed increased mitochondrial swelling, perinuclear localization, and disturbed fission and fusion. Genes involved in mitochondrial complex I and V function and fusion/fission events were significantly downregulated. Significant structural and functional differences between mtDNA H vs. J haplogroup transmitochondrial RPE cybrids.